An Empirical Investigation on Funding Liquidity and Market Liquidity - Chung, Ji-Yeong; Ahn, Dong-Hyun; Baek, In-Seok; Kang, Kyu Ho (Review of Finance, 2018)
In empirically exploring the link between funding liquidity and market liquidity, the greatest challenge is to designate a suitable market that shows such linkages. In this respect, the 15-year Japanese floating (JF)-rate bond market, characterized by the lack of diversity among highly leveraged trading strategies, is an ideal case for investigation. A clean measure of market liquidity, liquidity discount rate (LDR), is estimated from JF prices and the LDR is found to be intertwined with funding liquidity only during the crisis. The deterioration of funding liquidity precedes that of the LDR, thus providing evidence of the outbreak of liquidity spiral.